HUBUNGAN ANTARA PERSEPSI ANAK TERHADAP PERAN ORANG TUA DALAM PEMILIHAN PASANGAN HIDUP DENGAN KECENDERUNGAN PEMILIHAN PASANGAN HIDUP BERDASARKAN STATUS SOSIAL EKONOMI PADA DEWASA AWAL - Putri Saraswati (University of Merdeka Malang, 2011)
Abstract This study aims to determine the relationship between daughters perception to the role of parents in mate-selection with the tendency of mate-selection based on socio-economic status in early adulthood.In order to achieve its objectives, the research is conducted to early adult female whose parents play a role in determining the criteria for their daughters future husband.The research method is quantitative research method, which is the collection of data in numerical form.The data was collected by conducting surveying techniques, employing questionnaire of the daughters perception to the role of parents in mate-selection and questionnaire of the tendency of mate-selection based on socio-economic status.The collected data were analyzed by employing statistical techniques of product-moment correlation with the assistance of SPSS program for windows version 12 of 2003. Based on the research results, it is known that the p value of 0.001 and r value of 0.259, which means there is a weak relationship between daughters perception to the role of parents in mate-selection with the tendency of mate-selection based on socio-economic status in early adulthood. Keywords: early adulthood, the daughters perception to the role of parents in mate-selection, the tendency of mate-selection based on socio-economic status.